2017
DOI: 10.1111/eos.12395
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract induces oral squamous cell carcinoma cell invasion in a receptor for advanced glycation end‐products‐dependent manner

Abstract: . Cigarette smoke extract induces oral squamous cell carcinoma cell invasion in a receptor for advanced glycation end-products-dependent manner. Eur J Oral Sci 2018; 126: 33-40. © 2017 Eur J Oral SciOral squamous cell carcinoma (OSCC) affects approximately 30,000 people and is associated with tobacco use. Little is known about the mechanistic effects of second-hand smoke in the development of OSSC. The receptor for advanced glycation end-products (RAGE) is a surface receptor that is upregulated by second-hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Advanced glycation end-products (AGE) are formed from reducing sugars and biomolecules such as proteins, lipids, and nucleic acids by a sequence of nonenzymatic glycation reactions, collectively known as the Maillard reaction [26,31]. Exogenous sources of AGE originate from diet [32] and tobacco smoking [33]. Endogenously, AGE formation is promoted by hyperglycemia, but also by high levels of oxidative stress [26].…”
Section: Uremic Inflammationmentioning
confidence: 99%
“…Advanced glycation end-products (AGE) are formed from reducing sugars and biomolecules such as proteins, lipids, and nucleic acids by a sequence of nonenzymatic glycation reactions, collectively known as the Maillard reaction [26,31]. Exogenous sources of AGE originate from diet [32] and tobacco smoking [33]. Endogenously, AGE formation is promoted by hyperglycemia, but also by high levels of oxidative stress [26].…”
Section: Uremic Inflammationmentioning
confidence: 99%
“…However, the effect of smoking on RAGE signaling is less well studied. It was shown that stimulation of gingival carcinoma epithelial cells with cigarette smoke extract (CSE) increases RAGE expression and the subsequent inflammatory reaction and induces oral squamous cell carcinoma cell invasion [6]. Furthermore, it was shown that RAGE knock-out mice had reduced cigarette smoke-induced neutrophilic airway inflammation [7].…”
Section: To the Editormentioning
confidence: 99%
“…The RAGE is a pattern-recognition cell-surface receptor that experiences increased expression during exposure to tobacco smoke (Chapman et al, 2018;Robinson, Stogsdill, Lewis, Wood, & Reynolds, 2012;Winden et al, 2014). Expression of RAGE has been detected in gingival tissues from human subjects with chronic periodontitis and it is overexpressed in gingival tissues from smokers diagnosed with periodontal diseases (Chapman et al, 2018).…”
mentioning
confidence: 99%